Convergence Analysis of Parareal Algorithm Based on Milstein Scheme for Stochastic Differential Equations (Journal of Computational Mathematics, 2020)
In this paper, we propose a parareal algorithm for stochastic differential equations(SDEs), which proceeds as a two-level temporal parallelizable integrator with the Milsteinscheme as the coarse propagator and the exact solution as the fine propagator. The convergence order of the proposed algorithm is analyzed under some regular assumptions.Finally, numerical experiments are dedicated to illustrating the convergence and the convergence order with respect to the iteration number $k$, which show the efficiency of theproposed method.